2023
DOI: 10.3390/ijms241310654
|View full text |Cite
|
Sign up to set email alerts
|

Advances on the Study of Diurnal Flower-Opening Times of Rice

Abstract: The principal goal of rice (Oryza sativa L.) breeding is to increase the yield. In the past, hybrid rice was mainly indica intra-subspecies hybrids, but its yield has been difficult to improve. The hybridization between the indica and japonica subspecies has stronger heterosis; the utilization of inter-subspecies heterosis is important for long-term improvement of rice yields. However, the different diurnal flower-opening times (DFOTs) between the indica and japonica subspecies seriously reduce the efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…In indica rice varieties diurnal flower opening time, otherwise known as floret-opening time begin around 10 am (Wang et al, 2022;Wang et al, 2023). We reported that heat tolerant varieties grown under LHS maintained lower canopy temperature−not just during the crucial daytime flowering period of 10 am to 12 pm, but throughout the entire day and night−compared to heat susceptible varieties grown under the same scenario.…”
Section: Discussionmentioning
confidence: 94%
“…In indica rice varieties diurnal flower opening time, otherwise known as floret-opening time begin around 10 am (Wang et al, 2022;Wang et al, 2023). We reported that heat tolerant varieties grown under LHS maintained lower canopy temperature−not just during the crucial daytime flowering period of 10 am to 12 pm, but throughout the entire day and night−compared to heat susceptible varieties grown under the same scenario.…”
Section: Discussionmentioning
confidence: 94%